Con no sé qué vislumbres de ironía: indicators and marks of irony in Viaje del Parnaso (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
This article analyzes the irony present in Viaje del Parnaso from a pragmalinguistic perspective. After a summarized explanation of the literary problems that the piece of work under consideration –which has almost unanimously been classified as burlesque poetry– has caused, linguistic conception has been applied to the strategy used by Cervantes, emphasizing the irony as an element of parody and satire as well as a polyphonic or echoic technique. Thus, this piece of work is classified as a continuous unstable or heuristic irony, in which some indicators or marks that enable an accurate interpretation of the Cervantine tercets are visible. Among these indicators or marks, alarm words, euphemisms, word plays and epistemic modalization stand out.
Keywords: Irony; Mockery; Polyphony; Pragmatics